2019
DOI: 10.1016/j.ab.2019.02.031
|View full text |Cite
|
Sign up to set email alerts
|

AFFINImeter: A software to analyze molecular recognition processes from experimental data

Abstract: The comprehension of molecular recognition phenomena demands the understanding of the energetic and kinetic processes involved. General equations valid for the thermodynamic analysis of any observable that is assessed as a function of the concentration of the involved compounds are described, together with their implementation in the AFFINImeter software.Here, a maximum of three different molecular species that can interact with each other to form an enormous variety of supramolecular complexes are considered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 23 publications
(55 reference statements)
0
79
0
Order By: Relevance
“…The integrated heat data generated a binding isotherm with a single inflection point, and a mild slope ( Figure 2 A, right panel and Table 1 ). The fit of the obtained data, performed using the AFFINImeter software [ 49 ] and a model involving a single set of sites, showed that two Ni(II) ions bind per Hp UreG monomer with similar affinity ( K d = 72 µM), a favorable enthalpic contribution and a minor entropic impact ( Table 1 ). Previously reported studies on Hp UreG mutants indicated that at least one Ni(II) binding site is located on the CPH motif [ 20 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The integrated heat data generated a binding isotherm with a single inflection point, and a mild slope ( Figure 2 A, right panel and Table 1 ). The fit of the obtained data, performed using the AFFINImeter software [ 49 ] and a model involving a single set of sites, showed that two Ni(II) ions bind per Hp UreG monomer with similar affinity ( K d = 72 µM), a favorable enthalpic contribution and a minor entropic impact ( Table 1 ). Previously reported studies on Hp UreG mutants indicated that at least one Ni(II) binding site is located on the CPH motif [ 20 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Displacement ITC experiments were performed to measure arginine binding in S69A; in this case, a sample of protein 100 μ m + histidine 4 m m was titrated with arginine 4 m m . Data were analyzed using the software Affinimeter . K d , the enthalpy change (∆ H ), and the binding stoichiometry ( n ) were determined by nonlinear fitting of the normalized titration data based on a 1 : 1 binding model (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting heat signals were integrated to give the heats per injection. The correlation of the heats per injection with the molar ratio of Lewis base andb orane gave ab inding isotherm (Figure 2c), which was analyzed with a1 :1 interaction model, [15] to derive the associationc onstants, K B .T hreei ndividual ITC experiments for each Lewis acid/Lewis base combination were performed. These individual resultsw ere averaged to determine the equilibriumc onstant, K B .T hus, ITC allowed equilibrium constants to be reliably determined in the range of 10 3 < K B < 10 7 m À1 .H owever,o ur ITC instrument could not be operated under completely inert conditions, and side reactions with traces of moisture werealimitation for boranes more acidic than 1e.…”
Section: Determination Of Equilibrium Constantsmentioning
confidence: 99%